PENGARUH LATIHAN SIRKUIT TRAINING TERHADAP DAYA TAHAN PEMAIN FUTSAL PSSP KUANSING - Ozi pebri Dwi Putra; Slamet Slamet; Adriah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the information with the trainer and the field observation that the futsal team PSSP KUANSING still not maximal in mastering futsal game. As well as researchers see the physical condition of team players futsal PSSP KUANSING still far from expected, it is evident from almost every championship team players futsal PSSP KUANSING often experience a decrease in physical conditions such as endurance during the match. This is evident from the match that was done for 2x 20 minutes. The purpose of this study is to determine the effect of training circuit training on the durability of futsal players PSSP KUANSING2. population in this study is ats futsal PSSP KUANSING amounted to 10 people. Sampling technique is by sampling saturation is the technique of determining the sample when all members of the population used as a sample. To obtain the desired data, the authors use a tool to collect data in this study is a 2.4 km run. Obtained in the analysis using the t-test. Based on the results of this study, a t test that produces t count of 8.837 with ttable 1.833 is accepted, at alpha level (0.05) It can be concluded that there is influence of training sircuit training on endurance In Futsal players PSSP KuansingKeywords: Circuit Training, Endurance